A comparative analysis of EU and US trade policies towards least developed countries and the African Growth and Opportunity Act beneficiaries. (15th July 2020) - Davies, Elwyn; Nilsson, Lars
Abstract: Motivation: The European Union (EU) and the US have specific trade preference programmes in place directed towards developing countries in general and, primarily in the case of the EU, towards least developed countries (LDCs) in particular. This article examines the relative merits of these programmes. Purpose: The article compares the trade policies of the EU and the US with respect to LDCs and the countries eligible for the US African Growth and Opportunity Act (AGOA) and examines the relative success of the two donors' trade policies vis‐à‐vis these two groups of beneficiaries in terms of increasing imports from them. Approach and methods: Econometric evidence from a gravity model is used to compare the effects of EU and US preferential trade policy on imports from the beneficiary countries. First, regressions are carried out using total EU and US imports as dependent variables and, second, EU and US duty‐free imports are used. Findings: The descriptive part of the article shows that (a) a larger share of EU imports benefits from duty‐free MFN tariffs; (b) the EU offers preferences on all imports from the LDCs (except arms and ammunition), while the US extends preferences to three quarters of all imports; (c) EU preferences are better utilized; and (d) the EU imports more goods duty free. The econometric analysis shows that EU trade policy towards the LDCs and the AGOA beneficiaries has generated approximately twice as much in imports as US policy, when imports of mineral fuels are excluded from the analysis. Policy implications: EU trade policy is found to outperform US trade policy in terms of generating imports from the LDCs and the AGOA beneficiaries. Hence, if any trade policy ought to be copied by other countries, as suggested by some observers, it should be EU trade policy rather than US trade policy.